ID23‐2: an automated and high‐performance microfocus beamline for macromolecular crystallography at the ESRF. Corrigendum. (14th March 2022) - Nanao, Max; Basu, Shibom; Zander, Ulrich; Giraud, Thierry; Surr, John; Guijarro, Matias; Lentini, Mario; Felisaz, Franck; Sinoir, Jeremy; Morawe, Christian; Vivo, Amparo; Beteva, Antonia; et al.
Abstract : Corrections to Table 2 of Nanao et al. [ J. Synchrotron Rad. (2022). 29, 581–590 ] are reported. Abstract : A revised version of Table 2 of Nanao et al. [ J. Synchrotron Rad. (2022). 29, 581–590 ] is provided.